Microaggressions on Campus: An Examination of Student Perceptions - Witherup, Kirsten L.; Verrecchia, P.J. (International Journal of Criminology and Sociology, 2019)
Creating and maintaining a positive school climate is paramount for student well-being. Microaggressions, or subtle forms of prejudice, in the classroom setting can present a barrier to cultivating such a climate and contribute to a host of negative consequences for impacted students. This study explores student perceptions of the prevalence and types of microaggressions at a private, liberal arts college in South-Central Pennsylvania. Data from student surveys will be examined to develop a better understanding of this topic and generate discussions about maintaining a positive and inclusive school climate that welcomes diversity.